Impact of Work Environment on Employees’ Performance in Federal Polytechnic, Offa, Kwara State, Nigeria - Afolabi, Olaunkanmi Muftau; Abiola, Bolaji Ibrahim; Olaiya, Abiodun Lukuman; Emeje, Susan Omotivie (NIU Journal of Social Sciences, 2020)
This study examined impact of work environment on employee performance using academic staff in Federal Polytechnic Offa, Kwara State as study focus. Survey research design was adopted with the use of questionnaire for data collection from the academic staff in the polytechnic. Data analysis was carried out with inferential statistics (regression and correlation matrix) and results established that the polytechnic work environment has significant effect on academic staff teaching effectiveness and that of research output. It was discovered that academic staff teaching potency is weak and research output is low. The study concluded that the polytechnic work environment has not promoted effective teaching and quality research. It was recommended that management should reposition the polytechnic work environment and make it more supportive to the academic staff performance especially in the areas of proper illumination and ventilation of lecture rooms, provision of internet facility, class control, lecturer/students ratio and conducive office arrangement. Keywords : Academic staff, Effective teaching, Performance, Research output, Work environment